Efektivitas Layanan Bimbingan Kelompok dengan Teknik Sosiodrama untuk Meningkatkan Komunikasi Asertif pada Remaja di Panti Asuhan Aisyiyah Putri Kupang - Tokan, Sri Yulia Putri; Korohama, Katharina E. P; Masi, Lolang Maria (Prodi Bimbingan Konseling FKIP UNDANA, 2025)
Assertive communication is communication that is honest, direct and firm without demeaning or hurting other people’s feelings. The lack level of asertive communication that occurs among teenagers at the Aisyiyah Putri Kupang orphanage is a case that needs to be improved, because if this is allowed to continue it will have a negative impact on their social relationships. This research aims to determine the description of the group guidance process using sociodrama techniques, assertive communication and the extent of the effectiveness of group guidance using sociodrama techniques to increase the sense of assertive communication in Adolescents at the Aisyiyah Orphanage, Kupang City. This research uses a quantitative approach with a pre-experimental research type with a one group pre test and post test research design. This research was carried out at the Aisyiyah orphanage. The sampling technique used is method purpose sampling that is, samples are taken according to the aims and objectives of the research pretest will be given to all members of the population, totaling 36 adolescent pasticipants, from the result pretest adolescent who show intensity of the sample will be 10 adolescent. The data collection technique uses a guestionnaire. The data analysis technique used is descriptive analysis, hypothesis testing (difference test) with the help of the program SPSS For Windows 25 Version. The results of this research show that in general assertive communication among adolescents falls into the low category, with 16 adolescents ( 45,72%) in the low category and 1 odolescents (2,78%) in the very low category. The analusis results show that the calculated Fvalue is 30.376, which is greater than the Ftable = 2.26, with a significance level of 0,000<0,05. Based on the regression value obtained in the test, it was found that 28% of the variation is explained, the anlysis was conducted by comparing the r table value at a 5% significance level and n= 36, which is 0,329 the while remaining 72% ia influenced by other factors. Based on the research results, it can be concluded that by communicating aggressively, students are better able to express their needs, desires and feelings in a healthy way, thereby reducing the possibility of aggressive behavior that is detrimental to themselves and others.